2022
DOI: 10.3389/fmicb.2022.822689
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Bacterial Resistance to Antibiotics in Food Animals

Abstract: The overuse of antibiotics in food animals has led to the development of bacterial resistance and the widespread of resistant bacteria in the world. Antibiotic-resistant bacteria (ARB) and antibiotic-resistant genes (ARGs) in food animals are currently considered emerging contaminants, which are a serious threat to public health globally. The current situation of ARB and ARGs from food animal farms, manure, and the wastewater was firstly covered in this review. Potential risks to public health were also highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 151 publications
1
27
0
Order By: Relevance
“…Skarżyńska et al (2020) assessed the AMR epidemiology in different animal species, including farm and wild animals, and found that tetracycline resistance was occurring in almost all tested animals, followed by the resistance to macrolides, aminoglycosides, and β-lactams. Not surprisingly, our findings are comparable with the findings of the previous studies that tetracycline resistance is most targeted, followed by macrolide and beta-lactam resistance in different food animals (Mehdi et al 2018;Skarżyńska et al 2020;Ma et al 2021aMa et al , 2021bXu et al 2022). This is in agreement with the most reported antimicrobials used in food-animal production systems, namely, tetracycline, sulfonamides, β-lactams aminoglycoside, and penicillin (Kimera et al 2020;Ma et al 2021b).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Skarżyńska et al (2020) assessed the AMR epidemiology in different animal species, including farm and wild animals, and found that tetracycline resistance was occurring in almost all tested animals, followed by the resistance to macrolides, aminoglycosides, and β-lactams. Not surprisingly, our findings are comparable with the findings of the previous studies that tetracycline resistance is most targeted, followed by macrolide and beta-lactam resistance in different food animals (Mehdi et al 2018;Skarżyńska et al 2020;Ma et al 2021aMa et al , 2021bXu et al 2022). This is in agreement with the most reported antimicrobials used in food-animal production systems, namely, tetracycline, sulfonamides, β-lactams aminoglycoside, and penicillin (Kimera et al 2020;Ma et al 2021b).…”
supporting
confidence: 92%
“…The prevention of AMR is associated with the One Health concept, which states that human health is related to the health of animals and the environment (Mackenzie and Jeggo 2019). Xu et al (2022) investigated the most prevalent ARB and ARGs in the farm animals considered a tremendous ARB and ARGs reservoir. They found that most resistance is to β-lactams (bla), aminoglycosides (aac), tetracyclines (tet), sulfonamides (sul), macrolide-lincosamide-streptogramin B (MLSB; erm), FCA (fluoroquinolone, quinolone, florfenicol, chloramphenicol, and amphenicol; fca), vancomycin (van), colistin (mcr), and multidrugs (mdr) (Xu et al 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Infections caused by antimicrobial-resistant bacteria represent one of the greatest threats to global health, accounting for approximately 1.2 million deaths per year from a worldwide perspective [ 1 , 2 ]. Campylobacter jejuni is the most prevalent zoonotic bacterial pathogen associated with foodborne gastroenteritis worldwide and represents a major recent challenge due to the increasing development of outbreaks associated with strains resistant to the drugs of choice for treatment, which include fluoroquinolones and macrolides.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of antibiotics is one of the greatest milestones in the history of human medical, meanwhile, that have promoted the rapid advancement in animal production. Statistics predict that up to 200,235 tons of antibiotics will be used in food animals to promote the growth of animals and to prevent bacterial infections in 2030, but most of them are not absorbed by animals and are excreted via feces and urine, which can directly contaminate and harm the surrounding environment (Xu et al, 2022 ; Li et al ). Even worse, the heavy misuse of antibiotics undoubtedly also contributes to the emergence of multidrug-resistant (MDR) bacteria, and results in a potential global health crisis.…”
mentioning
confidence: 99%